The Use of Systemic Treatment in the Maintenance of Patients with Non–Small Cell Lung Cancer: A Systematic Review. Issue 7 (July 2016) - Kulkarni, Swati; Vella, Emily T.; Coakley, Nadia; Cheng, Susanna; Gregg, Richard; Ung, Yee C.; Ellis, Peter M.
ABSTRACT : Introduction: : Non–small cell lung cancer (NSCLC) is often diagnosed at later stages when treatment options are limited. Maintenance therapy may prolong the time to disease progression and potentially increase overall survival. Secondarily, it may increase the proportion of patients eligible for second‐line therapy at the time of progression. The objective of this systematic review was to examine the use of systemic treatment in the maintenance of patients with NSCLC. Methods: : MEDLINE, EMBASE, and the Cochrane Library were searched for phase III randomized controlled trials comparing maintenance systemic treatment against another systemic treatment or placebo in patients with stage IIIB or IV NSCLC who had received a minimum of four prior cycles of platinum‐based chemotherapy. Meta‐analyses were conducted with clinically homogenous trials. Results: : Fourteen randomized controlled trials with 22 publications were included. The overall survival benefit was strongest for maintenance therapy with pemetrexed for patients with nonsquamous NSCLC (hazard ratio = 0.74, 95% confidence interval: 0.64–0.86) but not significant for patients with squamous NSCLC. There was also an overall survival benefit with maintenance therapy with epidermal growth factor receptor tyrosine kinase inhibitors, but the magnitude of the benefit was smaller than with pemetrexed (hazard ratio = 0.84, 95% confidence interval: 0.75–0.94). Docetaxel or gemcitabine as maintenance chemotherapies did not have an impact on overall survival. Conclusion: : For patients with advanced, stable stage IIIB/IV NSCLC whose disease has not progressed after four to six cycles of platinum‐based chemotherapy, the overall survival benefits were strongest for pemetrexed maintenance therapy followed by epidermal growth factor receptor tyrosine kinase inhibitor maintenance therapy.